HUBUNGAN PENGEMBANGAN KARIR DAN STRES KERJA DENGAN KINERJA KARYAWAN PADA PT XYZ - Amelia Dhea; Kristin Handayani (Jurnal Manajemen, 2020)
Employee performance plays an important role in supporting the enlargement of a company's business unit. In fact, the decrease in net profit margin of PT. XYZ during the period 2015 to 2018 by 3%, on the one hand, provides the fact that there was an increase in employee overtime by 700%. One of the factors determining performance is work motivation while one of the performance indicators is workload. The research objective was to determine the existence of a relationship between career development and job stress and employee performance at PT XYZ. The research object was 60 respondents of PT. XYZ. Samples were taken using non-probability sampling with saturated sampling techniques. Primary data collection using a questionnaire method. The data analysis technique used SPSS 20 software through descriptive analysis, pre-test of validity and reliability, classical assumption test, along with simple correlation coefficient analysis and multiple correlation coefficient. The results showed (1) there is a relationship between career development and employee performance, (2) there is a relationship between job stress and employee performance and (3) there is a relationship between career development and work stress together with employee performance. The conclusion of this research is that career development and job stress have a significant relationship with employee performance. Providing training to improve employee skills, communication between management and employees as well as attention in job analysis in the form of weighting the tasks given in a given span of time equitably related to the quality of employee work. Keywords: Career Development, Job Stress, Employee Performance